Protection Efforts of Lutjanus bohar (The Two-Spot Red Snapper) Spawning Area in Hoga Island Waters, Kaledupa-Wakatobi National Park - Muhajirin; La Ode Orba; La Ode Sahari (Jurnal Penelitian Kehutanan Wallacea, 2020)
A spawning area of Lutjanus bohar, a marine fish of high economic value, is one of the eight important resources of Wakatobi and also a critical habitat in the waters of Hoga Island. For protecting the area, Wakatobi National Park has stated the area as a tourism zone (no-take zone). This research was conducted to evaluate progress toward spawning-area protection by examine number of individuals, length size of fish, and trespassing cases that occurred in the spawning area. Research was carried out in 2018-2019. Number of individuals and size of fish werecollected by referring to the monitoring guidelines for the Spawning Aggregation Site (SPAGs), and observations with an Underwater Visual Census. Trespassing case data were collected by interview key persons. Descriptive analysis was used to describe progress toward spawning-area protection. The results indicate that the protection effort of spawning area has a positive impact in increasing number of individuals and length of Lutjanus bohar. However, number of trespassing cases in the waters of Hoga Island still shows an increase. Fishing activities are the most trespassing cases occurred in thespawningarea. This approach should be implemented to evaluate the progress towards protection efforts, besides increasing the number of patrols and socialization with fishermen to increase their awareness.